State of burns management in Africa: challenges and solutions - Lindert, Judith Anne Teresa; Bbaale, Dorothy; Mohr, Christoph; Chamania, Shobha; Bandyopadhyay, Soham; Boettcher, Johannes; Katabogama, Jean Bosco; Alliance, Bisimwa Wani; Elrod, Julia (Burns, 2023)
Introduction - Understand the availability of human resources, infrastructure and medical equipment and perceived improvement helps to address interventions to improve burn care. - Methods - Online survey covering human resources, infrastructure, and medical equipment of burn centers as well as perceived challenges and points for improvement. The survey was distributed in English and French via snowball method. Descriptive statistics and AI-based technique random forest analysis was applied to identify determinants for a reduction of the reported mortality rate. - Results - 271 questionnaires from 237 cities in 40 African countries were analyzed. 222 (81.9 %) from countries with a very low Human Development Index (HDI) (4th quartile). The majority (154, 56.8 %) of all responses were from tertiary health care facilities. In only 18.8 % (n = 51) therapy was free of charge for the patients. The majority (n = 131, 48.3 %) had between 1 and 3 specialist doctors (n = 131, 48.3 %), 1 to 3 general doctors (n = 138, 50.9 %) and more than 4 nurses (n = 175, 64.6 %). A separate burn ward was available in 94 (34.7 %) centers. Regular skin grafting was performed in 165 (39.1 %) centers. Random forest-based analysis revealed a significant association between HDI (feature importance: 0.38) and mortality. The most important reason for poor outcome was perceived late presentation (212 institutions, 78.2 %). The greatest perceived potential for improvement was introduction of intensive care units (229 institutions, 84.5 %), and prevention or education (227 institutions, 83.7 %). - Interpretation - A variety of factors, including a low HDI, delayed hospital presentation e.g. due to prior care by non-physicians and lack of equipment seem to worsen the outcome. Introduction of an intensive care unit and communal education are perceived to be important steps in improving health care in burns.